2021
DOI: 10.1002/mds.28749
|View full text |Cite
|
Sign up to set email alerts
|

Polyglutamine‐Expanded Ataxin‐3: A Target Engagement Marker for Spinocerebellar Ataxia Type 3 in Peripheral Blood

Abstract: Background: Spinocerebellar ataxia type 3 is a rare neurodegenerative disease caused by a CAG repeat expansion in the ataxin-3 gene. Although no curative therapy is yet available, preclinical gene-silencing approaches to reduce polyglutamine (polyQ) toxicity demonstrate promising results. In view of upcoming clinical trials, quantitative and easily accessible molecular markers are of critical importance as pharmacodynamic and particularly as target engagement markers. Objective: We aimed at developing an ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…In our 6-month-old Q84 animals, we found that higher plasma polyQ-ATXN3 levels correlated with a thinner molecular layer thickness at the cerebellar posterolateral fissure and a decrease in the overall time the mice spent mobile in the open field assay. Plasma polyQ-ATXN3 levels did not correlate with polyQ-ATXN3 levels in the forebrain in the Q84 mice ( Supplementary Figure S10 ), and this is perhaps consistent with human studies showing that plasma polyQ-ATXN3 levels do not associate with levels in the CSF ( Prudencio et al, 2020 ; Hubener-Schmid et al, 2021 ). Overall, while preliminary, our findings suggest that plasma polyQ-ATXN3 levels can correlate with disease features in mice and warrant its further investigation as a biomarker in human SCA3.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In our 6-month-old Q84 animals, we found that higher plasma polyQ-ATXN3 levels correlated with a thinner molecular layer thickness at the cerebellar posterolateral fissure and a decrease in the overall time the mice spent mobile in the open field assay. Plasma polyQ-ATXN3 levels did not correlate with polyQ-ATXN3 levels in the forebrain in the Q84 mice ( Supplementary Figure S10 ), and this is perhaps consistent with human studies showing that plasma polyQ-ATXN3 levels do not associate with levels in the CSF ( Prudencio et al, 2020 ; Hubener-Schmid et al, 2021 ). Overall, while preliminary, our findings suggest that plasma polyQ-ATXN3 levels can correlate with disease features in mice and warrant its further investigation as a biomarker in human SCA3.…”
Section: Discussionsupporting
confidence: 79%
“…While we did not detect any correlations between CSF or plasma polyQ-ATXN3 levels and disease features in patients in our initial study ( Prudencio et al, 2020 ), we did detect an association between urine polyQ-ATXN3 levels and an earlier age of onset in a follow-up report ( Koike et al, 2021 ). A separate study using a slightly different immunoassay noted a correlation between plasma polyQ-ATXN3 levels and disease severity, but also failed to see a correlation between CSF polyQ-ATXN3 levels and disease features ( Hubener-Schmid et al, 2021 ). In our 6-month-old Q84 animals, we found that higher plasma polyQ-ATXN3 levels correlated with a thinner molecular layer thickness at the cerebellar posterolateral fissure and a decrease in the overall time the mice spent mobile in the open field assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HD [31][32][33] and SCA3 [34,35], immunoassays based on the TR-FRET technology were already established to quantify the respective disease protein in human leukocytes, mononuclear cells (PBMCs) or human tissue samples. Later, the TR-FRET-based immunoassays were further developed into ultra-sensitive single molecule counting (SMC) immunoassays in order to be able to quantify fmol protein amounts in CSF and peripheral blood of HD and SCA3 mutation carrier, too [36,37]. Following it's successful establishment in HD and SCA3, the polyQ-expanded ATXN2 protein should also be validated as potential prognostic and therapeutic biomarker in SCA2.…”
Section: Discussionmentioning
confidence: 99%
“…For other polyQ diseases like HD [31][32][33] or SCA3 [34,35], TR-FRET-based immunoassays for quanti cation of polyQ-expanded disease proteins, like huntingtin or ataxin-3, have been established. Additionally, to detect very low protein concentrations in peripheral blood or CSF, ultrasensitive single molecule counting (SMC) immunoassays were validated [36,37] and used as prognostic and/or therapeutic readout parameters. In SCA2, the disease protein ATXN2 could also represent a potential prognostic and/or therapeutic biomarker, as the amount of polyQ-expanded ATXN2 in e.g., blood or CSF may re ect the course of the disease and potential therapeutic success.…”
Section: Introductionmentioning
confidence: 99%